The Relationship Between Peer Pressure With Bullying Behavior In Early Adolescents - Ikeu Nurhidayah; Karti Nur Aryanti; Iwan Suhendar; Mamat Lukman (Universitas Padjadjaran, 2021)
Bullying is a problem that often occurs worldwide, especially in the school environment and will cause various impacts. The effects of bullying on children include physical impacts (bruised and full of wounds) and psychological impacts (children are reluctant to go to school, feel embarrassed, and feel pressured). Peers greatly influence the occurrence of bullying behaviour in early adolescents. In the school environment, early teens always spend time with peers. The purpose of the study was to determine the relationship between peer pressure and bullying behaviour in early adolescents. This research method uses a descriptive-analytic with cross-sectional approach. The population in this study was the early adolescent of the junior high school students (SMPN 2 Tarogong Kidul Garut Regency), which obtained a sample of 88 students using the proportionate stratified random sampling technique. This study used the Peer Pressure Scale (PPS) and Adolescent Peer Relations Instrument (APRI) instruments. The analysis in this study uses univariate analysis to determine the frequency distribution and bivariate analysis using the Chi-Square test. The results in this study stated that there was a significant relationship between peer pressure and bullying behaviour (p-value=0.021). Therefore, nurses need to educate early teens about bullying behaviour and the importance of healthy peer relationships.